Efficacy of Apremilast Gels in Mouse Model of Imiquimod-Induced Psoriasis Skin Inflammation - Marcelle Silva-Abreu; Lilian Sosa; Lupe Carolina Espinoza; María-José Fábrega; María J. Rodríguez-Lagunas; Mireia Mallandrich; Ana Cristina Calpena; María Luisa Garduño-Ramírez; María Rincón (MDPI AG, 2023)
Apremilast (APM) is a novel drug for the treatment of psoriasis and psoriatic arthritis. APM is a phosphodiesterase 4 (PDE4) inhibitor, raising intracellular cAMP levels and thereby decreasing the inflammatory response by modulating the expression of TNF-α, IL-17, IL-23, and other inflammatory cytokines. The goal of this study is to develop APM gels as a new pharmaceutical formulation for the treatment of topical psoriasis. APM was solubilized in Transcutol-P and incorporated into Pluronic F127, Sepigel, and carbomer bases at different proportions. All formulations were characterized physiochemically. A biopharmaceutical study (release profile) was performed, and ex vivo permeation was evaluated using a human skin model. A toxicity assay was carried out on the HaCaT cell line. A mouse model of imiquimod-induced psoriasis skin inflammation was carried out to determine its efficacy by histological analysis, RNA extraction, and RT-qPCR assays. APM gel formulations showed good physicochemical characteristics and a sustained release profile. There was no permeation of any gel measured through human skin, indicating a high retained amount of APM on the skin. Cell viability was greater than 80% at most dilution concentrations. APM gels treated the psoriasis mouse model, and it shows a reduction in the proinflammatory cytokines (IL-8, IL-17A, IL-17F, and IL-23). APM gels could be a new approach for the treatment of topical psoriasis.